METABOLIC CHARACTERISTICS OF LEAN AND OVERWEIGHT ADOLESCENTS DIAGNOSED WITH PCOS - Diana-Irina Buiuca; D.M. Preda; L. Zuga; I.M. Stefanescu; A. Mirica (Romanian Journal of Oral Rehabilitation)
Aim of the study: This study aims to investigate the prevalence of lean and excess weight adolescents with PCOS and to examine the metabolic characteristics such as dyslipidemia and insulin resistance across both weight categories. Methods: This cross-sectional study observed 68 patients between 11 and 20 years of age with diagnosed with PCOS. All patients provided detailed medical history, underwent clinical examination, and assessment of hormonal and metabolic parameters. Results: Of the 68 patients, 39.7% were lean (<85 percentile: 5.9% underweight and 33.8% normal weight), while 60.3% were excess weight (≥85 percentile: 19.1% overweight and 41.2% obese). Moderate-severe hirsutism was seen in 50% of adolescents with PCOS, with hirsutism being more severe in excess weight adolescents (P=0.025). Dyslipidemia was seen in 16.2% of patients, with 11.1% of lean and 19.5% of excess weight patients being dyslipidemic. Insulin resistance (HOMA-IR >2) was seen in 6% of patients, all patients with increased HOMA-IR were of excess weight. Acanthosis nigricans was seen in 15% of patients (24.4% of excess weight patients, 0% of lean patients) (P=0.05). Conclusions: These findings contribute to broadening the understanding of polycystic ovarian syndrome and its associated metabolic risk in order to inform early intervention recommendations in both lean and excess weight adolescents.